Leveraging Wildlife Tourism for Employment Generation and Sustainable Livelihoods: The Case of the Kgalagadi Transfrontier Park, Southern Africa - Tichaawa, Tembi M.; Lekgau, Refiloe J. (Bulletin of Geography. Socio-economic Series, 2020)
This study examined the contribution of wildlife tourism and conservation to employment generation and sustainable livelihoods of a community residing adjacent to the Kgalagadi Transfrontier Park, Southern Africa. Adopting a qualitative approach, semi-structured interviews were conducted with tourism stakeholders and focus group discussions with members of the community. The findings reveal wildlife tourism to have positively contributed towards providing diverse employment opportunities for the community. Additionally, the livelihood diversification strategies largely involved integrating the cultural and natural resources with the wilderness experience of the region. However, a major concern is the significant lack of linkages between wildlife tourism and the local economy of the community. While the study concludes wildlife tourism to be an important economic sector for the community, it recommends further integration of micro and small local businesses into wildlife tourism so as to enhance the contribution of the Park and wildlife tourism to community livelihoods.